The Right to Education in Brazil: An Analysis of the Current Legislation on Homeschooling (CIPEEX, 2025)
The present paper has as justification to reinforce the debate of ideas about Homescholing in Brazil, because every day the number of families that search for this education system has been increasing. The Federal Supreme Court has already considered the matter to have general repercussions (RE 888815 RG / RS), so that the issue is extremely relevant to Brazilian society, especially in view of the general decadent aspect of public education in Brazil. The STF indicated that the matter was not foreseen in the current Brazilian legislation, denying that there is a subjective right to home education, although signaling that the Federal Constitution does not prohibit its effectiveness, depending only on an eventual law that regulates the offer. The general objective is to seek to discuss whether the Homescholing modality is valid in Brazil when confronted with the Federal Constitution, so that the State, in recurring moments, makes interventions inappropriately or not in the family right to provide home education to its children.